2006
DOI: 10.1525/sop.2006.49.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Parental Involvement, Family Structure, and Adolescent Sexual Decision Making

Abstract: This study uses data from the National Longitudinal Study of Adolescent Health to determine what aspects of parental involvement are related to sexual initiation, whether parental involvement explains the association between family structure and sexual debut, and whether these relationships differ among boys and girls or among non-Latino/a white, African American, and Latino/a adolescents. Results indicate that among young women and non-Latino/a white adolescents, four aspects of parental involvement-shared di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 51 publications
3
82
1
1
Order By: Relevance
“…Researchers have investigated the association between social structures, such as peers, family, schools, and the media, and the timing of first sex (e.g., Hawkins, Catalono, Kosterman, Abbott, & Hill, 1999;L'Engle & Jackson, 2008;Pearson, Muller, & Frisco, 2006). There is evidence that all of these are associated with differences in age of sexual debut, and that these associations vary as a function of adolescents' age, ethnicity, and gender.…”
Section: Sexual Debutmentioning
confidence: 99%
“…Researchers have investigated the association between social structures, such as peers, family, schools, and the media, and the timing of first sex (e.g., Hawkins, Catalono, Kosterman, Abbott, & Hill, 1999;L'Engle & Jackson, 2008;Pearson, Muller, & Frisco, 2006). There is evidence that all of these are associated with differences in age of sexual debut, and that these associations vary as a function of adolescents' age, ethnicity, and gender.…”
Section: Sexual Debutmentioning
confidence: 99%
“…However, results from longitudinal studies contradict these findings and demonstrate that family configuration does not influence the decision of adolescents to initiate sexual life (Pearson, Muller, & Frisco, 2006) or the quality of their romantic relationships (Valle & Tillman, 2014). In support of the hypothesis that family transition is not in itself a negative life event, other studies have found that family configuration does not influence the perceived social support (Pérez Milena et al, 2007).…”
mentioning
confidence: 95%
“…Parental involvement has been linked to decreased risky sexual behavior (Pearson, Muller, & Frisco, 2006), higher rates of academic achievement (Fan & Chen, 2001), and social and behavioral success in school settings (El Nokali, Bachman, & Votruba-Drzal, 2010). Most relevant to the current study, parental involvement is also negatively associated with anxiety and depressive symptoms (Colder et al, 1997;Duchesne & Ratelle, 2010).…”
Section: Supportive Parentingmentioning
confidence: 99%